Validation of the patient measure of safety (PMOS) questionnaire in Australian public hospitals. (3rd December 2019) - Taylor, Natalie; Clay-Williams, Robyn; Ting, Hsuen P; Winata, Teresa; Arnolda, Gaston; Hogden, Emily; Lawton, Rebecca; Braithwaite, Jeffrey
Abstract: Objective: Patients can provide a unique perspective on the safety of care in hospitals. Understanding that the extent to which the way hospitals are organized for quality and safety is associated with patient perceptions of care is becoming increasingly valued and necessary for the direction of targeted interventions across healthcare systems. The UK-developed patient measure of safety (PMOS) assesses eight domains of ward safety from the patient point of view and has recently been adapted and piloted in Australia. The aim of this study is to test the psychometric properties of PMOS-Australia (PMOS-A) amongst a large cohort of hospitalized patients. Design: Cross-sectional questionnaire validation assessment. Setting and participants: As part of the DUQuA project, the PMOS-A survey was distributed within acute myocardial infarction, hip fracture and stroke departments across 32 large public hospitals in Australia. Patients could complete the PMOS-A independently, or request the assistance of a family member/guardian, or staff on the wards—space was included to record mode of completion. Main outcome measures: Confirmatory factor analysis (CFA) was undertaken on a calibration sample to generate the model, and a validation sample was used to cross-validate the model. A subset of only those participants who received assistance for PMOS-A completion was also tested using CFA on a calibration and validation sample. Model fit indices (chi-square to degrees of freedom ratio [Chi-square:DF], root mean square error of approximation [RMSEA], comparative fit indices [CFI], standardized root mean squared residual [SRMR]), Cronbach's α, average inter-item correlations, construct reliability and cross-loadings were examined with reference to recommended thresholds to establish the extent of convergent validity and discriminant validity. A marker of criterion validity was assessed through testing associations between the PMOS-A and adherence to clinical guidelines. Results: Across the calibration and validation samples of the full ( N =  911) and assisted completers only subset ( N =  490), three (Chi-square:DF, SRMR, RMSEA) of the four indices consistently or almost always met thresholds for acceptable model fit. CFI indices did not meet the recommended limits (0.72–0.78, against a target > 0.9). Positive relationships were found for all tests between PMOS-A and adherence to clinical guidelines, and these were significant when assessed in the calibration datasets for the full and assisted completion samples. Conclusion: A sufficiently reliable and valid measure of patient perceptions of safety has been developed. These findings should provide adequate support to justify the use of this measure to assess patient perceptions of safety in Australian hospitals and can be modified for use elsewhere.